2016
DOI: 10.1073/pnas.1611723113
|View full text |Cite
|
Sign up to set email alerts
|

Antigen exposure shapes the ratio between antigen-specific Tregs and conventional T cells in human peripheral blood

Abstract: The T-cell receptor (TCR) is required for maturation and function of regulatory T cells (Tregs), but the ligand specificities of Tregs outside the context of transgenic TCRs are largely unknown. Using peptide-MHC tetramers, we isolated rare specific Foxp3 + cells directly ex vivo from adult peripheral blood and defined their frequency and phenotype. We find that a proportion of circulating Tregs recognize foreign antigens and the frequency of these cells are similar to that of selfreactive Tregs in the absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 46 publications
4
35
1
Order By: Relevance
“…Previous reports demonstrate that a minor fraction of Foxp3 + Treg cells can be identified within antigen-specific T cell populations reactive to both self and foreign pMHC-II (Malhotra et al, 2016; Moon et al, 2011; Su et al, 2016). However, these populations do not reflect naturally occurring antigen specificities that drive the robust selection of Treg cells in the thymus.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports demonstrate that a minor fraction of Foxp3 + Treg cells can be identified within antigen-specific T cell populations reactive to both self and foreign pMHC-II (Malhotra et al, 2016; Moon et al, 2011; Su et al, 2016). However, these populations do not reflect naturally occurring antigen specificities that drive the robust selection of Treg cells in the thymus.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, T reg cells generated in the perinatal period persist and effectively inhibit autoimmunity throughout life 51 . The overall frequency of the polyclonal T reg cell population is approximately 5–15% of CD4 + T cells, but the ratio between antigen-specific T reg and effector T cells decreases during an ongoing immune response, presumably to improve anti-pathogen immunity 52 . T reg cells may also promote tissue repair in response to inflammatory factors released from damaged cells 53 and exert a regenerative effect in the CNS 54 and skeletal muscle 55 .…”
Section: The Conundrum Of Strongly Self-reactive Treg Cellsmentioning
confidence: 99%
“…Using tetramers to directly identify and characterize endogenous self antigen-specific T cells, we and others have revealed that the impact of deletion on peripheral frequencies of self antigen-specific T cells is much less complete than previously anticipated [8][9][10][11]. Moreover, Foxp3 + Tregs comprise only a minor fraction of these cells, leaving open the question of how Foxp3 − conventional cells remain tolerant in the steady state [8][9][10]12].…”
Section: Introductionmentioning
confidence: 95%